Multimetallic intra-nanogap nanozyme-mediated lateral flow immunoassay for ultrasensitive and multimode detection of K. pneumonia in clinical samples - Zhi, Weixia; Guo, Xinjie; Nie, Yichu; Nie, Lu; He, Tingting; Dai, Li; Xu, Jing; Zong, Xiangxin; Xu, Jun; Cai, Huaihong; Tang, Yong; Cong, Yanguang; et al. (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
The current lack of rapid screening methods for Klebsiella pneumonia (K. pneumonia) poses a considerable threat to human health. Herein, we fabricated a multilayer Au@Au@Ag/Pt nanoparticle (NP) that made of the peroxidase-mimicking external shell and tunable plasmonic intra-nanogap as a versatile probe, and conjugated them with lateral flow immunoassay (LFIA) for colorimetric-catalytic-SERS (CM/CL/SERS) multi-model sensing K. pneumonia in complex biological matrix. After the optimization of several parameters, the limit of detection (LOD) of the target K. pneumonia were 103 CFU/mL for CL-LFIA and 38 CFU/mL for SERS-LFIA, both of which were over 10-fold and 200-fold more sensitive than the visual CM-LFIA (104 CFU/mL), respectively. The clinical validation of this multi-model LFIA was performed with the infected patients (N = 6) and healthy subjects (N = 3), among which 4 positive samples missed by conventional CM-LFIA were successfully identified by SERS-LFIA. More importantly, this LFIA has great specificity for the target bacteria, while showed no signal response to samples infected by other bacteria. Different from previous studies focusing on detection of protein and nucleic acid of K. pneumonia, our study shortened the sample-to-answer time with direct detection of K. pneumonia by LFIA, filling the diagnostic gap for point-of-care testing (POCT) of K. pneumonia infection. Overall, the great performance of our established LFIA suggested its substantial potential for diagnosis of K. pneumonia-induced nosocomial infection. •A multilayer Au@Au@Ag/Pt nanoparticle featured with plasmonic properties and peroxidase-like activity was proposed.•This LFIA immunoassay is especially suitable for diagnosis of patients who have mild bacterial infection in the early stage.•Colorimetric/catalytic/SERS multi-model sensing can overcome the problem of insufficient adaptability of a single signal.•This LFIA can distinguish the infected patients from healthy subjects with great accuracy.